Differences in retinal shape between East Asian and Caucasian eyes. (29th March 2017) - Verkicharla, Pavan K.; Suheimat, Marwan; Schmid, Katrina L.; Atchison, David A.
Abstract: Purpose: To investigate whether retinal shape is different between East Asians and Caucasians. Methods: There were 36 East Asian and 40 Caucasian young adults, with refractions between +0.75D and −5.50D. Peripheral eye lengths were obtained after pupil dilation using the Lenstar partial coherence interferometer. Measurements were obtained along the horizontal and vertical meridians of the visual field out to ±35° and ±30°, respectively, in 5° steps. Retinal co‐ordinates were estimated using a validated method from the peripheral eye length measurements and ray‐tracing through a modified Le Grand full theoretical eye. Rays were directed normally towards the anterior cornea. Retinal shapes were described in terms of vertex radius of curvature ( R v ), asphericity ( Q ) and equivalent radius of curvature ( R E q ) along both horizontal and vertical meridians. Results: R v was smaller in East Asian than in Caucasians (mean difference ± 95% CI −0.7 ± 0.5 mm), along the horizontal meridian than the vertical meridian (−1.2 ± 0.6 mm), and in myopia than in emmetropia (−1.0 ± 0.6 mm). R v along the horizontal meridian, but not along the vertical meridian, became smaller as myopia increased. Q did not vary significantly with meridian, refraction group or race. The same pattern of results occurred for R E q as for R v . The percentage differences of heights under the estimated retinal surfaces showed steeper retinas in East Asians than in Caucasians; the differences between East Asian and Caucasian emmetropes were 2.5% and <1% along horizontal and vertical meridians, respectively, and corresponding differences for myopes were 4.6% and 1.8%. Conclusion: East Asians had steeper retinas than Caucasians. The horizontal meridian had steeper retinas than the vertical meridian. Myopes had steeper retinas than emmetropes. Racial differences in retinal shape in both emmetropes and myopes, combined with the high prevalence of myopia in East Asia, suggest that retinal shape may play a role in myopia development.